Semantic Ambiguity in English: A review on Lexical, Structural, and Scope Challenges in Communication - Rim Mohammed Abdalla Lasheiky (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2024)
Due to the possibility of various meanings, semantic ambiguity particularly in English presents a serious obstacle to efficient communication. This study investigates key types of semantic ambiguity linguistic, structural, and scope and their influence on comprehension. Lexical ambiguity occurs when words have multiple meanings or sounds, leading to misunderstandings in both speech and writing. Structural ambiguity happens when sentence structure allows for different interpretations, while scope ambiguity arises from shifts in meaning related to negation and qualification. This research reviews past studies and theories, such as the exhaustive access hypothesis, which downplays context, and the context-dependency hypothesis, which stresses its importance in resolving ambiguity. The study emphasises the intricate relationship between context and meaning by examining examples like homonyms, polysemy, homographs, and homophones. Findings indicate that while ambiguity can disrupt understanding, background knowledge and contextual clues often enable listeners and readers to grasp intended meanings. Additionally, ambiguity is sometimes purposefully employed in literature, highlighting the critical role of context in resolving semantic ambiguity in communication.